Profile of Pancasila Students in Al-Farabi's Educational Philosophy - Muhammad Khakim Ashari; Moh Faizin; Usman Yudi; Yahya Aziz (At Turots: Jurnal Pendidikan Islam, 2023)
One of the famous Muslim philosophers among Muslims is al-Farabi who lived in the Middle Ages. Al-Farabi wrote many works numbering in the hundreds. Through various thoughts and the fruits of his work which were then followed and continued to be studied by subsequent generations to the present. However, not many of his works have been found in their entirety, of the hundreds of works produced, only a few have been preserved and can be studied to this day. A number of his works have been re-translated into several world languages, therefore his thoughts are widely spread throughout the world because they are studied by many groups. The description in this paper is to discuss al-Farabi's various theories related to Islamic educational philosophy, starting from thoughts about God, human beings, reason, the nature of education, educational material or curriculum, and also a discussion of al-Farabi's educational philosophy of thought. This research is included in the research library research. The data from this study came from books, journals and various articles related to the research theme. Data analysis in this study uses content analysis. The result of this study is that in viewing Islamic education, al-Farabi must integrate theoretical knowledge and implement educational values ​​at a practical level. Human success in achieving happiness in the world and the hereafter is determined by both, namely the integration of knowledge and noble morality. Al-Farabi when viewed from the perspective of Islamic educational philosophy, he is a figure with the al-diniy al-'aqlaniy or religious-rational wing. Al-Farabi's thoughts also correlate with the values ​​in the profile of Pancasila students, namely the aspects of faith and fear of God Almighty and noble character, as well as aspects of critical thinking.